MEDIEVAL ARABIC GEOGRAPHICAL TEXTS AND MAPS - Nadirova , Г.; Hanayi, O. (Journal of Oriental Studies, 2024)
Over the centuries, the interest of scholars in Arabic medieval sources on geography and geographical maps has been growing. This is connected with the important contribution of the Arab-Muslim civilization to the development of ideas about the inner and surrounding world, on the one hand, and the desire to restore or renew the history of various peoples involved in the zone of research interests of Arabic-speaking geographers, on the other hand. The authors of the article considered the sources stored in European repositories, available for study thanks to the descriptions and publications of Western orientalists, while discovering some trends manifested in the academic traditions of different stages of the development of historical geography. The interest of scientists of the 19th century was directed primarily to medieval texts, which were considered the primary and most important object for research, and the establishment of their authenticity was perceived as the main task of critical analysis of their content. As for maps, only in recent decades, did the historical and cultural context of this pictorial genre begin to be interpreted by scholars in all their fullness and functionality and published in the form of atlases, books, and encyclopedias, inviting readers to immerse themselves in a re-evaluated cultural tradition. The article aims to determine the features of different approaches to the interpretation of geographical Arabic-language sources in European oriental studies. For this purpose, critical editions of the sources undertaken in the projects of the Leiden and Bodleian libraries were studied and their characteristics were revealed through historical and comparative methods of analysis. The general dynamics in understanding historical geography from primarily philological textological work to cultural and interdisciplinary reevaluation of medieval Islamic maps is noted. Keywords: historical geography, medieval sources, Arabic maps, Leiden collections, Bodleian editions